Desain Integrated Farming melalui Konsep Lumbung Mataram untuk Pariwisata dan Ketahanan Pangan di Kalurahan Sambirejo - Wibowo, Andi Prasetiyo; Murti, Desideria Cempaka Wijaya; Putra, Venansius Galih Perkasa (Jurnal Atma Inovasia, 2026)
Community engagement activities in Sambirejo Village aim to develop a sustainable farming concept rooted in the Lumbung Mataraman tradition while supporting local food security and agritourism potential. The program focuses on formulating the concept and design of an Integrated Farming System (IFS) on a one-hectare site that unifies food crops, horticulture, livestock, and aquaculture within a single operational framework. Core Lumbung Mataraman values—mutual cooperation, food independence, and environmental sustainability—serve as the conceptual basis for designing a community-driven agritourism model. Implementation adopts a participatory approach involving field data collection, initial stakeholder discussions, and collaborative concept development to ensure that local knowledge informs the proposed design. The completed project outputs include a master plan, land-use zoning strategies, and system-integration schemes that outline spatial and functional relationships across farming components. These design documents provide a strategic foundation for future implementation phases. Further activities, such as community outreach, technical training, and the application of appropriate technologies, are recommended to strengthen long-term program impact.